A Simple Refining Technique of Coconut Oil for Small Holder Industries - Sugeng Triyono; Agus Haryanto (Jurnal Keteknikan Pertanian, 2009)
A simple refining equipment and process for small holder industries of edible coconut oil has beeninvestigated. The equipment consisted of 20-L filtering and NaOH neutralization bottles. Filtration wasintended to remove impurities such as gums and pigment, while neutralization was to remove free fattyacids (FFA) and other non-fat materials. In the experiment, the crude coconut oil was found to have impurityof 0.16%, FFA of 8.02%, saponification number of 270, and water content of 0.33%. The results showed thateither granular activated carbon (GAC) or zeolite filtration can be chosen individually to remove physicalimpurity. The GAC or zeolite-filtered coconut oil contained impurity less than the SNI standard of 0.05%.In term of FFA; however, the NaOH neutralized coconut oil did not meet the SNI standard of 0.3%. AfterNaOH neutralization, the GAC filtered oil contained 1.20% FFA; while the zeolite filtered oil contained1.32%. These FFA contents were definitely higher than the SNI standard, but could satisfy APCC standardfor grade IV coconut oil which is 5%. The refined coconut oils could also satisfy the SNI standard ofsaponification number which is 196 – 206 at minimum. In term of water content, either the filtered or theneutralized oil could also satisfy the SNI standard of 0.3%. In short, the proposed technique could helpfarmers refine their raw coconut oil, and hopefully improve its marketability.Keywords : retining, coconut oil, small holder industryDiterima: 21 Oktober 2008; Disetujui: 18 Maret 2009